Malaria in travelers and local populations: Comprehensive study of incidence patterns and origin-based classification in Saudi Arabia - Basmah Alharbi; Mawahib Ahmed (PLoS ONE, 2025)
Background Malaria continues to pose a significant public health threat in the Kingdom of Saudi Arabia (KSA), despite ongoing control efforts. Most malaria cases in the KSA are associated with travelers arriving from malaria-endemic regions. The rationale for studying malaria in the KSA stems from the country’s goal to eliminate the disease and address the increased risk of imported cases, which is heightened by substantial migration and religious tourism. Methods This study aimed to assess the origins of malaria cases, the relative contribution of the different Plasmodium species involved, and the incidence rates across different age groups in the KSA. The Ministry of Health collected data on malaria cases in 13 administrative regions from January 2022 to December 2023. The chi-square test was used to analyze the data and determine the overall parameters and the rate of slide positivity. Results The findings indicated that “imported” malaria cases were the predominant type of disease in the KSA. Out of 1,453,451 febrile cases examined, 0.7% (10,779) were positive across the 13 regions. In 2022, 688,629 cases were examined, with 0.9% (6,460) being positive. In 2023, 764,822 cases were examined, with 0.6% (4,319) being positive. Among these regions, Jazan exhibited the highest incidence rates (59%), followed by Makkah (20%), with a statistically significant difference (P = 0.046) between the regions. Malaria incidence was higher in patients aged ≥15 years. This study found significant variations (P = 0.002) in malaria incidence rates among different Plasmodium species. Plasmodium falciparum exhibited the highest rate at 63.5%, followed by P. vivax - P. ovale at 33%, P. malariae at 0.5%, and mixed infections where more than one species is involved at 3%. Conclusion During the study period, imported malaria was the major type of malaria, especially in the Jazan region and Makkah. The highest incidence was caused by P. falciparum . These findings indicate the need for targeted interventions and public health strategies to mitigate the “imported” malaria burden, particularly among travelers.